Organização da informação e do conhecimento de documentos artísticos à luz da terminologia - Deliberali Maimone, Giovana; de Fátima Gonçalves Moreira Tálamo, Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Introduces the field of Information Organization and Knowledge with the allowance of the disciplines of Applied Linguistics and Terminology in order to deepen the foundations of terminology research for documentary purposes. Justified the effectiveness of the relationship between terms in thesauri to enable better access to art museums documents. The research problem is based in the alternative informational possibilities in relation to the representative restriction of some thesauri, and are presented as examples of the Art and Architecture Thesaurus (AAT) and the system of classification Iconclass. Proposed improvements are carried out in order to highlight the importance of the Organization of Information and Knowledge for communication and knowledge generation in the museum context. The subjective interpretation of the individual must be respected in the museum, providing greater possibilities of information retrieval from the proper representation of documents.